2014
DOI: 10.1136/archdischild-2013-305165
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ventilator strategies and outcomes in preterm infants

Abstract: Despite a stable baseline risk, from 2006 to 2010, we observed a lower level of invasiveness, a reduction of mechanical ventilation and an increase of NIV use, and this was accompanied by a decrease in risk-adjusted mortality and BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
1
28
2
2
Order By: Relevance
“…However, the number of days on mechanical ventilation ranged up to 50 days and 60 days in the low-and high-dose vitamin D group, respectively, which was within the time period of documented increased serum 25(OH)D levels. A decreased need of mechanical ventilation is an important finding, as even modern invasive ventilator treatment for preterm neonates is associated with an increased risk of complications including BPD (67,99). One other RCT has reported on a lower risk of preterm birth in mothers with resultant higher 25(OH)D, adjusted for race, but gave no lung disease data (100), whereas another smaller RCT of smaller size with later gestational age at enrollment found no difference in gestational age at delivery (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of days on mechanical ventilation ranged up to 50 days and 60 days in the low-and high-dose vitamin D group, respectively, which was within the time period of documented increased serum 25(OH)D levels. A decreased need of mechanical ventilation is an important finding, as even modern invasive ventilator treatment for preterm neonates is associated with an increased risk of complications including BPD (67,99). One other RCT has reported on a lower risk of preterm birth in mothers with resultant higher 25(OH)D, adjusted for race, but gave no lung disease data (100), whereas another smaller RCT of smaller size with later gestational age at enrollment found no difference in gestational age at delivery (43).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these perceived changes include better uptake of antenatal steroids, improved thermoregulation and oxygen titration at resuscitation, changes in respiratory management, and improved nutrition management. Reports from other networks or collaborative efforts have compared outcomes over time and showed mixed results some showing improved outcomes while others showing worsening outcomes …”
mentioning
confidence: 99%
“…Studies have shown that restricting the use of IMV is feasible in clinical practice and is associated with a reduction in the incidence of BPD [6,7]. Interestingly, none of these studies reported the impact of restricted use of IMV on NDI [5].…”
Section: Introductionmentioning
confidence: 99%